TAXI TRANSPORT SAFETY REQUIRES SYSTEM SOLUTIONS - N. O. Bludyan (Вестник СибАДИ, 2020)
Introduction. The article deals with the problems of ensuring the safety of passenger by taxis. The current system of regulation and organization of taxi transport in the Russian Federation and some foreign mega-cities is being analyzed. It is pointed out that the regulation of taxi transportation and the system of permits issuing to legal persons and individual entrepreneurs is not perfect. The analysis of the reasons for the fundamental changes in the business model of taxi transport in the conditions of operation of aggregators has been carried out. The importance of ensuring the safety of passenger taxis in the new conditions is stressed. The article analyzes the consequences of the emergence of aggregate taxi companies and their radical transformation of classical taxi transport.Materials and methods. Based on the analysis of international experience, the priority of taxi driver requirements in the world’s largest mega-cities is justified. A comparison of the safety of passenger taxis with road traffic accidents in Western Europe is given. On the basis of official statistics, the level of safety of passenger taxi transport in Moscow and in comparison with accidents in the Russian Federation has been decreasing in recent years. However, the Russian Federation has not been able to meet the requirements of the Russian Federation. It is stated that the social risk indicator in taxi transport in Moscow, Russia, exceeds the Russian level by about 300%. The correlation between the safety of transport in taxis and the income of taxi drivers has been shown.Results. As a result of the research carried out in Moscow, a mathematical relationship between the driver’s salary and earnings and the duration of work has been determined. The results of the research carried out in Moscow are as follows: The Russian Federation has taken a number of steps. The existing tariffs dictated by aggregators do not provide a minimum level of social income and force drivers to recycle, disrupt work and consequently increase the number of accidents. A review of foreign studies also showed that a reduction in the hourly income of taxi drivers leads to an increase in the number of crashes. The real incomes of taxi drivers in Moscow are shown as a result of the activities of aggregators. The commission of aggregators has grown 10-12 times in the years of their activity. Discussion. On the basis of the completed study conceptual approaches to improve the system of regulation of taxi activity in our country with the aim of increasing the safety of passenger transport are proposed. Changes to the current regulatory system should establish the legal status of transport order aggregators and their responsibility for the safety of passengers. The proposed system envisages a change in the authority for tariff regulation of taxi transport. The introduction of «access to the profession» of the driver and «access to the market» of business entities is envisaged.Conclusion. The introduction of a permitting system for aggregators based on their operational requirements and on mobile platforms (applications) will increase the safety of taxi transportation. This will also be facilitated by the requirements for the level of professionalism of drivers in the form of ‘an access to the profession’. The same is true for ‘access to a market’ of entities directly carrying passengers. The creation of digital profiles and the control of orders transferred by aggregators will prevent illegal traffic. The legal status of taxi drivers and the monitoring of their working conditions will make it possible to optimize tariff regulation and raise the level of pay. The proposed set of measures together will improve the safety of passenger taxis.